A New Subfamily of Glycoside Hydrolase Family 30 with Strict Xylobiohydrolase Function - Crooks, Casey; Bechle, Nathan J.; St John, Franz J. (Frontiers in Molecular Biosciences, 2021)
The Acetivibrio clariflavus (basonym: Clostridium clariflavum) glycoside hydrolase family 30 cellulosomal protein encoded by the Clocl_1795 gene was highly represented during growth on cellulosic substrates. In this report, the recombinantly expressed protein has been characterized and shown to be a nonreducing terminal (NRT) specific xylobiohydrolase (AcXbh30A). Biochemical function, optimal biophysical parameters, and phylogeny were investigated. The findings indicate that AcXbh30A strictly cleaves xylobiose from the NRT up until an α-1,2-linked glucuronic acid (GA) decorated xylose if the number of xyloses is even or otherwise a single xylose will remain resulting in a penultimate GA substituted xylose. Unlike recently reported xylobiohydrolases, AcXbh30A has no other detectable hydrolysis products under our optimized reaction conditions. Sequence analysis indicates that AcXbh30A represents a new GH30 subfamily. This new xylobiohydrolase may be useful for commercial production of industrial quantities of xylobiose.